A Psychoanalytic Feminist Reading of Ten Novels by Naguib Mahfouz Baharak - Rashti, Baharak Hoshyar (2006)
In this research, psychoanalytic feminists' contestations based on Sigmund Freud's and Jacques Lacan's theories will be underlined. The postulations of the psychoanalytic feminists will form three main themes of this research. These three themes are Women Defying the Patriarchy and The Patriarchy Regulating Women and The Manifestation of the Regulation of Women. These themes will help us illuminate the notion of women's threatening presence in Mahfouz's novels and the patriarchy's resisting the danger. Women's power to destabilise the structures of the patriarchal society will be expounded by referring to Luce Irigaray, Julia Kristeva, Judith Butler, Helen Cixous and Jessica Benjamin's hypotheses. It will be mentioned that through their connection to death, the reproductive ability, their jouissance, women are able to threaten the symbolic law. They even try to reach their intersubjectivity and become a woman which the symbolic world attempts to hinder. They can also make men dependent on them and make them feel impotent. Facing women's vigour, patriarchy's fear will also be highlighted and it will be explained that it endeavours to suppress women by assuming different roles for them such as satisfiers, virgin and whore figures, derelict and sacrificed. The symbolic world even tries to turn women to objects of exchange and desire, silence them and change them to phallic beings. This thesis will present the extend that Mahfouz's female characters can endanger the stability of the patriarchal world of his novel and how his male characters attempt to counter his women. In this research, men's objectification and controlling women through gaze will be elaborated and it will be mentioned that in order to resist men's voyeuristic pleasure veiling is advocated and the critics' ideas supporting and rejecting it will be discussed in general and in Egypt. Patriarchay's attaching value to virgins and girls deflowered outside marriage being devalued will also be discussed. The notion of prostitution will also be highlighted in order to show that women might go astray in their pursuit of independence and individuality. The hardship and torment that prostitutes encounter in the industry will also be expounded. These concepts along with rape will be explored in Naguib Mahfouz's novels.